Intelligent query feedback during visual XML query formulation - Ang, Min Hwee (2011)
The development of XML is well established and getting popular because of their simplicity, generality, and usability over the Internet. Despite the tremendous improvement of Visual XML Query Formulations, the user-friendliness of such software has been ignored.